Employability Skill Training Intervention in Higher Education in India: A Model Based Study - et. al., Dr. Kavitha Desai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The job-readiness among management graduates in India is a concern for higher education providers and employers who determine the two forces: supply and demand of job market. Higher Education Institutions (HEIs) are under pressure to provide training programmes that are more closely aligned with ‘employers’ needs’ in terms of employability skills. Hence, the focus of the current study is to assess the employability skill - gap and job readiness of management students. This study intends to develop an appropriate and logical ‘Employability Skills -Training intervention Model for business management students during their study period. The study employs multi-source data with mixed methodology (quantitative and qualitative) that increases concurrent validity and robust estimates. The outcome of this study would facilitate the HEIs to review and redesign the skill development programmes with a focus on accomplishing the balance among ‘Academic Skills’, ‘Technical Skills’ and ‘Employability Skills’. It would facilitate the HEIs to review and redesign the skill development programmes with a focus on accomplishing the balance among ‘Academic Skills’, ‘Technical Skills’ and ‘Employability Skills’.